Effects of Using Hazelnut Husk, Wood Shaving and of the Mixture at Different Thicknesses on Broiler Performances, Some Organ Weights, Foot-Pad Dermatitis and Litter Traits - Musa Sarıca; Kadir Erensoy (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the effects of the use of hazelnut husk (HH), wood shavings (WS) and the mixture of 50% hazelnut husk + 50% wood shavings (MIX) in two different thicknesses (4 and 8 cm) as a litter material in broiler production. The experiment was carried out as a factorial experimental design (3 litter type and 2 thickness) and stocking density was 10 chickens per m2. At 6 wk. of age, the effect of litter types and thicknesses on broiler live weights, feed efficiency, and livability, were not significant. Also, no differences were found in terms of gizzard, digestive tract, abdominal fat and edible internal organ weight percentages. While carcass yield varied between litter groups, there was no difference between litter thicknesses. The litter moisture levels at the end of the trial were not affected the litter type and litter thickness, while the foot pad dermatitis (FPD) rates were significantly affected. The highest FPD levels were determined in the HH litter and 4 cm thickness. As a result, the use of HH, WS and MIX of them with a thickness of 4 and 8 cm had no effect on other traits except for FPD levels. It has been observed that these litter materials may be used successfully in broiler production and use of 8 cm thickness litter has minor positive effects except that the cost of litter has doubled.